21. EXAMINATION OF MINIMUM INHIBITORY CONCENTRATION OF VANCOMYCIN AGAINST METHICILLIN-RESISTANT STAPHYLOCOCCUS AUREUS STRAINS ISOLATED AT DA NANG C HOSPITAL (Vietnam Journal of Community Medicine, 2024)
Background: Vancomycin has been the first choice antibiotic for the treatment of MRSA infections. The widespread use of vancomycin has resulted in a decrease in susceptibility to vancomycin in many countries. Many studies have reported the higher minimum inhibitory concentration of vancomycin for MRSA, the lower the success rate of treatment with vancomycin. Therefore, accurate determination of vancomycin MIC is a tool to accurately assess resistance and predict the clinical efficacy of antibiotics.Objective: Determination of MRSA rate and minimum inhibitory concentrations, MIC50, MIC90 of vancomycin against MRSA.Materials and method: Cross-sectional descriptive study on 202 S. aureus strains isolated from clinical specimens at Da Nang C Hospital from May 2022 to May 2024. MRSA was identified by placing cefoxitin paper discs on all S. aureus strains and vancomycin MIC was determined by E-test technique on MRSA strains.Results: The rate of MRSA isolated was 76.7%. MRSA was isolated highest in urine specimens, followed by pus, sputum, secretions, blood and catheters; in the Department of Surgery, Internal Medicine and Intensive Care was higher than in the Department of ENT and other departments, and was similar in men and women. The MIC of vancomycin at a concentration of 0.25 µg/ml was 0.65%; at a concentration of 0.5 µg/ml was 87.73%; at a concentration of 1 µg/ml was 10.97%; at a concentration of 2 µg/ml was 0.65%. The MIC50=0.5 µg/ml and MIC90=1 µg/ml. MRSA strains in blood, pus, secretions, urine and catheter specimens had MIC50=0.5 µg/ml and MIC90=0.5 µg/ml. MRSA strains in sputum specimens had MIC50=0.5 µg/ml and MIC90=1 µg/ml.Conclusions: MRSA was accounted for a high proportion and were found in many types of specimens and different departments. MRSA strains had vancomycin MICs within the sensitive range, in which 0.65% of strains had MICs=2 µg/ml. MRSA strains in blood, pus, secretions, urine and catheter specimens had MIC50=0.5 µg/ml, MIC90=0.5 µg/ml. MRSA strains in sputum specimens had MIC50=0.5 µg/ml, MIC90=1 µg/ml.
Keywords: MRSA; MIC; Vancomycin